The Sovereignty of the Indonesian State in Addressing Rohingya Ethnic Refugees - Maylissabet; Tomong, Ravee; Burhani, Nasih; Saifa Abudillah, Mohammad (TERAJU: Jurnal Syariah dan Hukum, 2025)
The humanitarian conflict affecting the Rohingya ethnic group in Myanmar continues to this day. The conflict, which began after Myanmar's independence in 1948, has resulted in millions of Rohingya fleeing to other countries, including those in Southeast Asia that border Myanmar. Indonesia is also one of the destination countries for refugees. Recently, news about the influx of Rohingya refugees in Indonesia has flooded the mass media and social media. To what extent does Indonesia have the authority to resolve the Rohingya refugee conflict? This study complements existing studies, which lack focus on Indonesia's sovereignty in handling the Rohingya refugee case. This problem formulation is divided into three questions. First, what is the history of the Rohingya ethnic conflict? Second, what has been the response and attention of the international community to Rohingya ethnic refugees? Third, to what extent does Indonesia's sovereignty resolve the Rohingya ethnic refugee issue? This study is a literature study conducted using qualitative research. The data used is secondary data, namely books, articles, news, and other literature. The analysis in this study uses the content analysis theory ( ). The results are as follows. First, the Rohingya ethnic group, which has long occupied Myanmar, which borders Bangladesh, has been massively discriminated against by other ethnic groups and the Myanmar government. Second, the international organisations involved in handling Rohingya refugees are ASEAN, UNHCR, OIC, IMO, and the UN. Third, Indonesia has the absolute sovereign right to determine its own policies in accordance with the principles of the second principle, Civilised Humanity.